1983
DOI: 10.1089/hyb.1983.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monoclonal Antibodies Against Cell Surface Molecules Associated with Cytotoxic Activity of Natural and Activated Killer Cells and Cloned CTL Lines

Abstract: Supernatants of hybridomas from fused spleen cells of mice immunized with either a T4+ or a T8+ CTL clone, were screened for their ability to inhibit the cytotoxic activity of the T4+ and the T8+ CTL clone. Eight monoclonal antibodies (MAbs) with blocking activity were obtained and a preliminary characterization of these antibodies was carried out. The MAbs SPV-L1 and SPV-L5 were found to react with thymocytes and all peripheral blood leukocytes. SPV-L1 and SPV-L5 precipitated a molecular complex consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(68 citation statements)
references
References 30 publications
1
67
0
Order By: Relevance
“…LFA-1 has been described to act as a cellular adhesion molecule with an important role in lymphoid cell-cell interac tions [13][14][15]. The anti-LFA-1 mAb used here did not block the adhesion of monocytoid cells to artificial substrates such as plastic surfaces (Table 3).…”
Section: Adhesion Of Monocytoid Cells To Endothelial Cellsmentioning
confidence: 86%
See 1 more Smart Citation
“…LFA-1 has been described to act as a cellular adhesion molecule with an important role in lymphoid cell-cell interac tions [13][14][15]. The anti-LFA-1 mAb used here did not block the adhesion of monocytoid cells to artificial substrates such as plastic surfaces (Table 3).…”
Section: Adhesion Of Monocytoid Cells To Endothelial Cellsmentioning
confidence: 86%
“…In addition, Dana et al described two functional domains in CR3, one involved in C3bi binding and the other in stimula tion of granulocyte adhesion-dependent functions [11]* LFA-1 is present on virtually all leukocytes [12,13], and acts as an adhesion molecule involved in cell-cell interactions [14,15]. Anti-LFA-1 mAb have been demonstrated to inter fere with the lytic activity of cytotoxic T lymphocytes (CTL) [13,15,16] and natural killer (NK) cells [13,[17][18][19] and are able to block T helper cell-monocyte-associated functions [2] by preventing cell-cell contact.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty |xl containing 0.4 [xCi = 14.8 kBq tritiated thymidine ([3H]dThd) was added during the last 4 h of incubation. The cultures were harvested with an automatic cell harvester, MASH-II, and counted as described previously [3].…”
Section: Lymphocyte Proliferation Assaymentioning
confidence: 99%
“…LFA-1 is expressed on lymphocytes, monocytes and granulocytes [1], whereas Mo-1 and pl50,95 are present on monocytes, granulocytes and "null" cells [2], Recently, it has been shown that these molecules contribute to the adhesion reaction of these cells. Blocking experiments with anti-LFA monoclonal antibodies (mAb) demonstrated that LFA-1 inhibits the adhesion step between effector and target cells in cytotoxic T lymphocyte, natural killer and lectin-dependent cellular cytotoxicity [1,3,4], LFA-1 also participates in monocyte-dependent lectin-induced T cell proliferation suggesting that it also acts as an adhesion molecule between monocytes and T cells. Mo-1, which is the receptor for the inactivated form of C3b, mediates the adhesion of soluble complexes or particles selec tively opsonized with C3bi [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation